The Eldon House diaries : five women's views of the 19th century - Harris, Robin S. (Robin Sutton), 1919-2000.; Harris, Terry G.; Knight, Charlotte Owen Harris, 1828-1854.; Champlain Society (Toronto, Ont. : Champlain Society in co-operation with the government of Ontario, 1994)
Edited from the diaries of Charlotte Owen Harris, 1848-1854; Amelia Ryerse Harris, 1857-1882; Sophia Howard Ryerson Harris, 1860-1861; Mary Elizabeth Lucy Ronalds Harris, 1868-1895; Amelia Archange Harris, 1882.
Includes bibliographical references (pages 499-508) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Harris family -- Diaries; Eldon House (London, Ont.); Harris family; Harris (Famille); Eldon House (London, Ont.); Harris (Famille) -- Journaux intimes; Harris family; Eldon House (London, Ont.); Women -- Ontario -- London -- Diaries; London (Ont.) -- Description and travel; Canadian diaries -- Ontario -- London; Femmes -- Ontario -- Journaux intimes; Femmes -- Ontario -- Biographies; Journaux intimes canadiens-anglais -- Ontario -- London; Femmes -- Ontario -- London -- Journaux intimes; Canadian diaries; Travel; Women; Ontario -- London; Alltag; Frau; Quelle; London (Ont.); Geschichte 1800-1900.; Diaries